Microeconomic foundations of Keynesian macroeconomics - Negishi, Takashi (Amsterdam : New York : North-Holland Pub. Co. ; New York : distributors for the U.S.A. and Canada, Elsevier North-Holland, 1979)
The book presents a non-Walrasian economic theory which can explain microeconomic aspects of Keynesian macroeconomic equilibrium with involuntary unemployment as well as to give a critical review of recent neoclassical theories which regard unemployment merely as a voluntary and temporary phenomenon
Includes bibliographies and indexes.
obn 24/01/2019
Loans
Keywords: Keynesian economics; Macroeconomics; Microeconomics